Effects of industrial by-product based geopolymers on the strength development of a soft soil - Yaghoubi, Mohammadjavad; Arulrajah, Arul; Disfani, Mahdi Miri; Horpibulsuk, Suksun; Bo, Myint Win; Darmawan, Stephen (Soils and foundations, 2018)
Portland cement is traditionally used as a binder in ground improvement projects on soft soil foundations. The use of cement in ground improvement projects, however, is fraught with both, financial and environmental concerns due to its relatively high cost, the use of natural resources and the high carbon footprint from cement production. Attempts are being made to find alternative environmentally friendly binders with a low carbon footprint using industrial by-products such as fly ash (FA) and slag (S). Using waste by-products such as FA and S to produce geopolymer binders, as novel green cementitious materials, may provide an environmentally friendly and effective ground improvement option. In this study, the effect of adding geopolymers to a soft soil was investigated for usage in deep soil mixing (DSM) applications. The soil was a soft marine clay known as Coode Island Silt (CIS). Different combinations of FA and S with six combinations of sodium and potassium based liquid alkaline activators (L) were added to the soil to study the effects on its engineering and chemical properties. These changes were evaluated via an unconfined compression strength (UCS) test, scanning electron microscopy (SEM) imaging and energy-dispersive X-ray spectroscopy (EDS) tests. The tests were conducted after 3, 7, 14 and 28 days of curing. Based on the results, the important role of L in strength development was studied, and the combination of 30% NaOH with 70% Na2SiO3 was found to achieve the highest strengths. Furthermore, increasing the S content was found to result in significant improvements in strength. The excellent correlation between strength and stiffness shown in the results are expected to help in the development of relationships for strength prediction of these green binders in geotechnical applications. This study shows that FA and S based geopolymers can be used as sustainable binders in DSM projects, with significant environmental benefits.